Prevalence of depressive symptoms among children and adolescents in china: a systematic review and meta-analysis - Jia Zhou; Yiang Liu; Jingyao Ma; Zizhao Feng; Jie Hu; Jia Hu; Bin Dong (BMC, 2024)
Abstract Background Depression is a significant health concern among children and adolescents. Previous epidemiological studies on depressive symptoms in this population have yielded inconsistent findings. This study aims to systematically estimate the prevalence of depressive symptoms among Chinese children and adolescents. Method A comprehensive literature search was conducted in both English (PubMed, EMBASE) and Chinese (China National Knowledge Infrastructure, WANFANG) databases from their inception until October 15, 2024. This meta-analysis employed a random-effects model to estimate the pooled prevalence of depressive symptoms. Results A total of 439 eligible studies, comprising 1,497,524 participants, were included in the analysis. The pooled point prevalence of depressive symptoms among children and adolescents was found to be 26.17% (95% CI 25.00-27.41%), with significant heterogeneity among studies (I2 = 100%, p < 0.001). The most commonly used scales were the SDS and CES-D; the SDS reported a higher prevalence (28.80%, 95% CI 26.88-30.85%) compared to the CES-D (24.50%, 95% CI 22.49-26.68%). There was no clear temporal trend in the prevalence of depressive symptoms over time (r = 0.03, P = 0.74). The highest pooled prevalence was observed in high school students (28.23%, 95% CI 25.58-31.15%), followed by undergraduate students (27.72%, 95% CI 25.79-29.79%) and middle school students (24.15%, 95% CI 21.61-27.00%). Among the provinces, Inner Mongolia exhibited the lowest prevalence (18.43%, 95% CI 11.98-28.36%), while Qinghai and Tibet had the highest rates at 54.19% and 47.50%, respectively, although only two and one study were included for these regions. Conclusions The detection rate of depressive symptoms in this study aligns closely with global rates for children and adolescents. High school students exhibit a higher prevalence of depressive symptoms compared to other age groups, highlighting the need for effective interventions targeted at this population. There was no clear temporal trend in the prevalence of depressive symptoms. Additionally, the choice of measurement tool is a critical aspect of epidemiological research; standardizing these measurements is essential for enhancing data comparability across studies. Trial Registration International Prospective Register of Systematic Reviews: No. CRD42023455604.